Social Participation of the Ranu Pane Village Community in the Village Tourism Area Development - Azmi, Sani Syauqi; Sri Giriwati, Novi Sunu; Aziz, Sri Utami (University of Merdeka Malang, 2021)
Ranu Pane Village is an enclave village located in the Bromo Tengger Semeru National Park area. This village still maintains the traditional Tengger culture which has natural potential in the form of Lake Ranu Pane and Lake Ranu Regulo. Located in a national strategic area of 10 priority tourist destinations, Ranu Pane village is directed to become a tourist village. Tourism development in the perspective of local independence is the embodiment of a community order that is carried out independently. Community participation is very decisive in the development of tourist villages, so as not to be separated from the cultural values of the local community and the decline in environmental quality, so that tourism management will be able to create a prosperous society together with nature conservation. This research is a qualitative descriptive study with direct observation techniques and library data collection. The purpose of this study was to determine the participation of the Ranu Pane village community in the development of a tourist village. through a SWOT analysis obtained a strategy for the development of tourist villages. In general, it is necessary to increase the participation of the village community so that it is better.